1992
DOI: 10.1055/s-2007-1021244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Visual Analogue Scale (VAS) and the Category Ratio Scale (CR-10) for the Evaluation of Leg Exertion

Abstract: Perceptual ratings given on the Visual Analogue Scale (VAS) and the Category Ratio Scale (CR-10) were compared in 24 healthy male volunteers (18-39 years) subjected to an exercise test using a bicycle ergometer. Ratings of leg exertion were made by means of the CR-10, the VAS and, as a complementary measure, the method of free magnitude estimation (ME). Blood lactate levels (BL) and heart rates (HR) were used as correlates to sensory perception. The correlation between the CR-10 ratings and BL at 180 W were .5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
51
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 1 publication
3
51
0
2
Order By: Relevance
“…subjectively during exercise exertion. 16,32 The changes in MVIC, ROM, and serum CK activity after eccentric exercise in our study were similar to those reported in previous studies 22,33 and indicate that muscle damage was induced by the exercise. The time course of the changes in VAS score and PPT was also similar to those reported after eccentric elbow-flexor exercise in previous research.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…subjectively during exercise exertion. 16,32 The changes in MVIC, ROM, and serum CK activity after eccentric exercise in our study were similar to those reported in previous studies 22,33 and indicate that muscle damage was induced by the exercise. The time course of the changes in VAS score and PPT was also similar to those reported after eccentric elbow-flexor exercise in previous research.…”
Section: Discussionsupporting
confidence: 81%
“…The level of muscle pain evoked by the standardized stimulus was assessed using a 100-mm VAS on which 0 indicated no pain and 100 represented extreme pain 28 and a CR-10 scale on which 0 indicated no pain and 10 represented maximal pain. 15,16 Each participant was asked to mark the level of perceived pain on the VAS, followed by the CR-10 scale (the 2 assessments were performed consecutively), when the investigator applied pressure to the biceps brachii at 3, 9, and 15 cm above the elbow crease. During the pressure assessment, the investigator placed his index and middle fingers over the site and applied pressure (approximately 35-40 kPa or 250 mm Hg) with the tips of the fingers toward the deeper tissues for 3 seconds.…”
Section: Muscle-pain Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has, however, been met with criticism, as has the assumption of congruence in meaning of scale values (Svensson, 1998(Svensson, , 2000Williams, Davies and Chadury, 2000). The VAS has also been found to be subject to end effects (Neely, Ljunggren, Sylvén and G. Borg, 1992;Neely and E. Borg, 1995).…”
Section: Category Scaling and Verbal Expressionsmentioning
confidence: 99%